2023
DOI: 10.3389/fmed.2023.1113460
|View full text |Cite
|
Sign up to set email alerts
|

Target therapy for high-risk neuroblastoma treatment: integration of regulatory and scientific tools is needed

Abstract: IntroductionSeveral new active substances (ASs) targeting neuroblastoma (NBL) are under study. We aim to describe the developmental and regulatory status of a sample of ASs targeting NBL to underline the existing regulatory gaps in product development and to discuss possible improvements.MethodsThe developmental and regulatory statuses of the identified ASs targeting NBL were investigated by searching for preclinical studies, clinical trials (CTs), marketing authorizations, pediatric investigation plans (PIPs)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 54 publications
0
0
0
Order By: Relevance
“…Neuroblastoma has significant clinical and biological heterogeneity, with some children having spontaneous regression without treatment and others having poor prognosis and extensive metastasis despite effective multimodal therapy [5]. The long-term survival rate of children with NB in the high-risk group is less than 50% despite aggressive multimodal therapy (radiotherapy, surgery, autologous stem cell transplantation, GD2 (disialoganglioside, GD2) monoclonal antibody, or maintenance therapy with retinoic acid) [4,[6][7][8][9][10][11]. Studies have shown that children with NB in the high-risk group are most likely to develop bone marrow metastasis, and children with NB in the high-risk group are highly susceptible to recurrence because of minimal residual disease (MRD) in the bone marrow [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%
“…Neuroblastoma has significant clinical and biological heterogeneity, with some children having spontaneous regression without treatment and others having poor prognosis and extensive metastasis despite effective multimodal therapy [5]. The long-term survival rate of children with NB in the high-risk group is less than 50% despite aggressive multimodal therapy (radiotherapy, surgery, autologous stem cell transplantation, GD2 (disialoganglioside, GD2) monoclonal antibody, or maintenance therapy with retinoic acid) [4,[6][7][8][9][10][11]. Studies have shown that children with NB in the high-risk group are most likely to develop bone marrow metastasis, and children with NB in the high-risk group are highly susceptible to recurrence because of minimal residual disease (MRD) in the bone marrow [12][13][14][15][16][17][18][19].…”
Section: Introductionmentioning
confidence: 99%